Scheduling data broadcast in asymmetric communication environments - Vaidya, Nitin H.; Hameed, Sohail (Wireless networks, 1999)
With the increasing popularity of portable wireless computers, mechanisms to efficiently transmit information to wireless clients are of significant interest. The environment under consideration is asymmetric in that the information server has much more bandwidth available, as compared to the clients. In such environments, often it is not possible (or not desirable) for the clients to send explicit requests to the server. It has been proposed that in such systems the server should broadcast the data periodically. One challenge in implementing this solution is to determine the schedule for broadcasting the data, such that the wait encountered by the clients is minimized. A broadcast schedule determines what is broadcast by the server and when. In this paper, we present algorithms for determining broadcast schedules that minimize the wait time. Broadcast scheduling algorithms for environments subject to errors, and systems where different clients may listen to different number of broadcast channels are also considered. Performance evaluation results are presented to demonstrate that our algorithms perform well.